Health Analysis of Private Banks during the Covid-19 Pandemic with the RGEC Approach - Suhartini*, Nani; Nurul Awaliah, Siti Farika (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
Covid-19 has had an impact on various sectors of life, including banking. This study aims to see the health condition of Bank Muamalat Indonesia with the RGEC approach. The indicators measured are risk profile, good corporate governance, earnings, and capital at Bank Muamalat Indonesia during the Covid-19 pandemic. The results showed that the health level of Bank Muamalat Indonesia was in the less healthy category with a value of 48.57% during the 2021-2022 period and 54.28% in the 2020 period. Bank Muamalat's problems occur in non-performing financing which is increasing, resulting in capital shortages and decreased bank profitability. In addition, the results of the study prove that the health of Bank Muamalat has decreased in the year of the observation period. However, the health of Muamalat Bank which is in the unhealthy category is contrary to the high customer loyalty. This is evidenced by the increasing ratio of liquidity to Third Party Funds and the awards obtained by Bank Muamalat in the category of customer satisfaction.